2021
DOI: 10.1111/1475-6773.13877
|View full text |Cite
|
Sign up to set email alerts
|

Association between nursing home staff turnover and infection control citations

Abstract: Objective: To describe the association between nursing home staff turnover and the presence and scope of infection control citations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…Nursing homes are required to submit daily employee-level staffing information based on auditable payroll and contract data to the PBJ, including unique employee identifiers (allowing individual staff members to be tracked over time), staff type, employment arrangement (salary or contract), and hours worked. 6 , 7 , 16 While the data cover a broad range of staff types, we restricted this analysis to nursing staff (RNs, LPNs, and CNAs) because these staff provide the majority of direct care for patients, and facilities may have deliberately reduced or deferred the use of other staff (eg, therapists, administrative staff) during outbreaks. These staff care for both short-stay and long-stay patients at nursing homes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing homes are required to submit daily employee-level staffing information based on auditable payroll and contract data to the PBJ, including unique employee identifiers (allowing individual staff members to be tracked over time), staff type, employment arrangement (salary or contract), and hours worked. 6 , 7 , 16 While the data cover a broad range of staff types, we restricted this analysis to nursing staff (RNs, LPNs, and CNAs) because these staff provide the majority of direct care for patients, and facilities may have deliberately reduced or deferred the use of other staff (eg, therapists, administrative staff) during outbreaks. These staff care for both short-stay and long-stay patients at nursing homes.…”
Section: Methodsmentioning
confidence: 99%
“…The nursing home industry has long been plagued by concerns about the adequacy and turnover of its staffing, 4 , 5 , 6 , 7 and anecdotal reports indicate that COVID-19 has placed immense additional strain on the industry’s workforce. 8 Staff have been at substantial risk of contracting COVID-19, in part owing to persistent personal protective equipment shortages and inadequate COVID-19 testing.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 29 studies examining registered nurse staffing, 19 reported higher levels of this staff grade and compliance were positively associated (15, 36, 47-49, 56-58, 79, 88, 90, 93, 113, 120, 138, 153-156) , nine reported a null association (16,52,61,65,92,96,124,126,157) and one reported a negative association. (87) Likewise, total nurse staffing levels (all grades of nurse staff) and compliance were positively associated in eleven studies (36,45,51,54,87,110,111,128,153,156,158) , with two finding a negative association (49,111) and three a null association. (37,72,84) The results are similar for nurse aides/care assistants: 15 studies reported higher levels these staff and compliance were positively associated (15,35,37,48,49,51,54,56,58,79,90,126,128,138,154,156) , nine reported a null association (16,…”
Section: Other: Staffingmentioning
confidence: 96%
“…Nurse turnover deteriorates the activities of daily living, worsens existing pressure ulcers, or causes the development of new pressure ulcers, and increases 30-day hospitalization rates, medical errors, and the possibilities of receiving infection control citations in the United States and South Korea [ 8 , 9 , 10 , 11 ]. In addition, high nurse turnover rates considerably increase costs.…”
Section: Introductionmentioning
confidence: 99%